A role for whey acidic protein four-disulfide-core 12 (WFDC12) in the pathogenesis and development of psoriasis disease - Zhao, Fulei; Zhang, Chen; Li, Guolin; Zheng, Huaping; Gu, Linna; Zhou, Hong; Xiao, Yuanyuan; Wang, Zhen; Yu, Jiadong; Hu, Yawen; Zeng, Fanlian; Wang, Xiaoyan; et al. (Frontiers in Immunology, 2022)
WAP four-disulfide core domain protein 12(WFDC12) has been implicated in the pathogenesis of psoriasis but the specific molecular mechanism is not clearly defined. In this study, we found the expression of WFDC12 protein closely correlated with psoriasis. WFDC12 in Keratinocyte might increase infiltration of Langerhans (LCs) and monocyte-derived dendritic cells (moDDCs), upregulating the co-stimulation molecular CD40/CD86. Th1 cells in lymph nodes were higher in K14-WFDC12 transgenic psoriasis-like mice. Meanwhile, the mRNA of IL-12 and IFN-γ in the lesion skin was significantly increased in transgenic mice. Moreover, we found that the expression of the proteins that participated in the retinoic acid-related pathway and immune signaling pathway was more changed in the lesion skin of K14-WFDC12 transgenic psoriasis-like mice. Collectively, the results implied that WFDC12 might affect the activation of the retinoic acid signaling pathway and regulate the infiltration of DC cells in the skin lesions and lymph nodes, thereby inducing Th1 cells differentiation and increasing the secretion of IFN-γ to exacerbate psoriasis in mice.